2019
DOI: 10.1007/s00253-019-09904-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol supplementation on the transcriptional landscape of bionanocellulose producer Komagataeibacter xylinus E25

Abstract: Ethanol exerts a strong positive effect on the cellulose yields from the widely exploited microbial producers of the Komagataeibacter genus. Ethanol is postulated to provide an alternative energy source, enabling effective use of glucose for cellulose biosynthesis rather than for energy acquisition. In this paper, we investigate the effect of ethanol supplementation on the global gene expression profile of Komagataeibacter xylinus E25 using RNA sequencing technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 80 publications
(105 reference statements)
3
51
1
Order By: Relevance
“…This solvent acts as an activator in cell growth and depending on the concentration may favor the production of bacterial cellulose 28,30 . This results in the effective use of glucose for the cellulose synthesis and not in its use for the acquisition of energy 31 . The great contribution of ethanol in the bacterial cellulose production can be seen in Figure 1, when graphically comparing the productions of biopolymer during the period from 0 to 240 h for culture media (A), (B) and (C).…”
Section: Kinetic Study Of the Mediummentioning
confidence: 99%
“…This solvent acts as an activator in cell growth and depending on the concentration may favor the production of bacterial cellulose 28,30 . This results in the effective use of glucose for the cellulose synthesis and not in its use for the acquisition of energy 31 . The great contribution of ethanol in the bacterial cellulose production can be seen in Figure 1, when graphically comparing the productions of biopolymer during the period from 0 to 240 h for culture media (A), (B) and (C).…”
Section: Kinetic Study Of the Mediummentioning
confidence: 99%
“…Therefore, the production process remains relatively expensive, which is mainly determined by high costs of cultivation media and other growth factors [ 12 ]. The wider commercial applications of BNC, including the food and paper industry, are hampered mainly due to the price [ 59 ]. Currently, various studies are being carried out in order to improve bacterial nanocellulose production to reduce operating costs and increase biocellulose synthesis yield [ 60 ].…”
Section: Bnc Production For Commercial Applicationsmentioning
confidence: 99%
“…The choice of parameters such as pH, temperature, incubation time, dissolved oxygen content, chemical composition of medium, culture methods (agitated or stationary cultivation), and other operational conditions play the key role in bionanocellulose production [ 12 , 60 ]. It has been shown that supplementation of the defined growth media with alternative substrates (e.g., ethanol, acetic acid, lactic acid, sodium citrate, vitamins, glycerol, polymers such as carboxymethylcellulose (CMC), or agar) can improve BNC biosynthesis [ 59 , 75 , 76 , 77 , 78 , 79 , 80 ]. Molina-Ramirez et al [ 75 ] reported the growth in bacterial nanocellulose yield up to 279% by the addition of alternative energy sources, such as ethanol and acetic acid to SH medium.…”
Section: Bnc Production For Commercial Applicationsmentioning
confidence: 99%
“…The type II operon ( bcsII ) is probably responsible for the production of acylated cellulose due to the presence of an acyltransferase gene within its structure (Umeda et al 1999 ). Expression of the cellulose biosynthesis operon was found to be constitutive, however shown to fluctuate depending on growth phase and environmental conditions (Augimeri and Strap 2015 ; Hernández-Arriaga et al 2019 ; Ryngajłło et al 2019a ). Cellulose synthase enzyme activation occurs at the posttranslational level and is mediated by c-di-GMP ( bis -(3′,5′)-cyclic di-guanosine-mono-phosphate), which binds to the PilZ domain of the BcsA subunit and activates it allosterically (Ross et al 1985 ; Fujiwara et al 2013 ; Römling et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first global transcriptome of a Komagataeibacter sp. has been published and involves the study of effect of ethanol supplementation in the culture of K. xylinus E25 (Kubiak et al 2014 ; Ryngajłło et al 2019a ). This study has expanded the understanding of the positive effect of ethanol on BNC synthesis by revealing the gene expression changes triggering this effect, such as up-regulation of UDP-glucose synthesis pathway and down-regulation of glycolysis and acetan biosynthesis.…”
Section: Introductionmentioning
confidence: 99%